2023
DOI: 10.1186/s13063-023-07361-6
|View full text |Cite
|
Sign up to set email alerts
|

The PRESIDE (PhaRmacogEnomicS In DEpression) Trial: a double-blind randomised controlled trial of pharmacogenomic-informed prescribing of antidepressants on depression outcomes in patients with major depressive disorder in primary care

Abstract: Background The evidence for the clinical utility of pharmacogenomic (PGx) testing is growing, and guidelines exist for the use of PGx testing to inform prescribing of 13 antidepressants. Although previous randomised controlled trials of PGx testing for antidepressant prescribing have shown an association with remission of depression in clinical psychiatric settings, few trials have focused on the primary care setting, where most antidepressant prescribing occurs. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Further, existing work has shown that the use of PGx testing results during prescribing had a positive, significant effect on patient recall of physician medication recommendations, which has the potential to contribute to a number of patient and medication experience components contributing to medication adherence, such as patient engagement [39]. Finally, an evaluation of the PGx effect on medication adherence for antidepressants is currently underway [40].…”
Section: Medication Experience Within Pgx Patient Experiencementioning
confidence: 99%
“…Further, existing work has shown that the use of PGx testing results during prescribing had a positive, significant effect on patient recall of physician medication recommendations, which has the potential to contribute to a number of patient and medication experience components contributing to medication adherence, such as patient engagement [39]. Finally, an evaluation of the PGx effect on medication adherence for antidepressants is currently underway [40].…”
Section: Medication Experience Within Pgx Patient Experiencementioning
confidence: 99%